LITERATURE REVIEW: PRAKTIK SUPERVISI EFEKTIF DALAM MENINGKATKAN MUTU PEMBELAJARAN - Syabirin; Marinu Waruwu; Halida Halida; Eny Enawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to review the literature on effective supervision practices in improving learning quality in educational institutions. The method used is a systematic literature review by analyzing articles, books and journals published in the last ten years. The data collection process was conducted through academic databases, and the literature results were analyzed thematically. The research found that effective supervision involves open communication between supervisors and teachers, a participatory approach, and the provision of constructive feedback. Continuous evaluation also plays an important role in teacher professional development and improving learning quality. The results of this study emphasize that supervision practices that are structured and supported by consistent planning and evaluation can significantly improve teacher performance and learning quality. However, there are challenges in its implementation, such as limited time and resources. In conclusion, effective supervision must be accompanied by adequate policy support to optimize learning outcomes.